Decision Support System SIM Card Provider Selection Using the Simple Additive Weighting Method - Vanny Fitria Ramadanti (Jurnal Teknik Informatika C.I.T Medicom, 2022)
Communication and information media is growing and continues to change over time. For example, in the past, letters were a medium for communicating, then they were replaced with pagers, public telephones, landlines, and now using mobile or cellular phones. Media information providers also continue to experience developments ranging from newspapers, magazines, television, and the internet. However, currently there are tools that can cover both functions, namely smartphones that can be used to communicate as well as access information. To support smoothness and convenience in communicating and accessing information via the internet, a Subscriber Identity Module Card or SIM card or starter pack is required. However, some consumers still find it difficult to determine which SIM card provider to use, even though this is of course very important to consider considering that the selection of this SIM card provider will determine the level of comfort and smoothness of communicating and surfing the internet without having to worry about billing costs and quotas. which is drained. This research was conducted with the aim of knowing which SIM cards are the most widely used today, providing information to users to be more familiar with the various types and brands of SIM cards issued by several providers, determining the best SIM card based on certain criteria to be a recommendation to consumers. users, and provide input to the provider company about what criteria are taken into consideration by users when choosing a SIM card. The study was conducted by using the weighted summation of the Simple Additive Weighting method to determine the best SIM card provider. The final result of the study obtained a value of 0.90 for SIM card provider Tri as a recommendation for the best SIM card provider.